The impact of the quality of accounting information on investment decisions: An applied study on a sample of companies listed on the Iraqi Stock Exchange (Entrepreneurship Journal for Finance and Business, 2025)
Accounting information is a vital element and an important basis in evaluating the performance of companies and an important tool in formulating their policies and making future decisions, especially with regard to investment decisions in securities, especially if this information is prepared in accordance with local or international principles and standards, which gives it quality and effectiveness in its use. The problem of the research lies in the accounting information is still unclear in the financial reports, which leads to difficulty for investors in making their investment decisions regarding buying and selling shares in the Iraqi Stock Exchange. The research aims to study the relationship and impact between the quality of accounting information and the investment decision-making process, and to highlight the importance of the accounting information contained in the reports. The financial statements of companies registered in the Iraqi stock market are for investors to help them make their investment decisions. In his study, the researcher used the questionnaire form method in collecting data. Among the most important results are: Individual Iraqi investors find that the accounting information contained in the financial reports is clear, understandable, and sufficient for the purpose of making their investment decisions. Iraqi individual investors need accounting information when making their decisions about buying and selling shares on the Iraqi Stock Exchange, and reading financial reports greatly affects their investment decisions. The most important recommendations: Work to increase individual investors’ awareness of the importance of the Board of Directors’ letter when making their investment decisions.